How to analyze exchange rates? The case of foreign exchange dealers in Moroccan trading rooms - LAMZOURI , Ahmed Amine (Revue Internationale des Sciences de Gestion, 2024)
This paper explores the Moroccan Dirham (MAD) analysis practice of foreign exchange dealers belonging to the nine banks with market maker status granted by The Moroccan central bank (Bank Al-Maghrib ) in a context of transition to a more flexible regime. The ultimate goal is to investigate and interpret the underlying process related to the behavior of exchange operators within their environment. The methodology of interview surveys was employed to gather verbatims for a purely qualitative content analysis. Our sample comprises six Moroccan exchange operators selected using the convenience non-probabilistic sampling method. The main results revealed that the analysis of the Moroccan Dirham value is a problem with two degrees of mobility: the EUR/USD exchange rate analysis and the liquidity analysis.